Consumers’ perception and experience in purchasing local fresh fruits from retail shops in Melaka Tengah, Melaka / Muhammad Firdaus Jaafar - Jaafar, Muhammad Firdaus (Faculty of Plantation and Agrotechnology, 2018)
Consumer behaviour towards the purchasing the fresh produce also was changed due to the wide array of attribute that influence their buying attitudes. Efforts to understand buying behaviour in purchasing food have been widely explored especially for the local fruits. This research was conducted to determine the consumers’ perception and experience in purchasing local fruit from retail shops in Melaka Tengah, Melaka. Three main objectives were highlighted from this study which is to anticipate the purchasing pattern of three local fruit (pineapple, mango and banana) in the population of Melaka Tengah, Melaka. A total of 150 respondents have been selected for the purpose of this study. Four analytical techniques have been used to interpret the result which is descriptive analysis, cross tabulation analysis, mean analysis and Exploratory Factor Analysis (EFA). The outcome from this study revealed that consumer more preferred on traditional retail format rather than modern traditional retail format while purchasing the local fruits. Atmosphere of the retail market, competitive price, customer services and availability of various goods were identified as key determinants for consumer choosing the retail format. In understanding the definition of quality, consumers list several descriptions to describe the quality of the fruit which is the freshness and safety guaranteed, intrinsic value like a taste, selection of varieties and value of purchases. Based on this study, there was need for retail formats’ managers to considered what actually consumers need and wants and equilibrium between modern and traditional retailers must be met to fulfil what consumers wants.